On the Gas-Phase Reactivity of Complexed OH+ with Halogenated Alkanes - Adlhart, Christian; Sekiguchi, Osamu; Uggerud, Einar (Chemistry : a European journal, 2005)
OH+ is an extraordinarily strong oxidant. Complexed forms (LOH+), such as H2OOH+, H3NOH+, or iron–porphyrin‐OH+ are the anticipated oxidants in many chemical reactions. While these molecules are typically not stable in solution, their isolation can be achieved in the gas phase. We report a systematic survey of the influence on L on the reactivity of LOH+ towards alkanes and halogenated alkanes, showing the tremendous influence of L on the reactivity of LOH+. With the help of with quantum chemical calculations, detailed mechanistic insights on these very general reactions are gained. The gas‐phase pseudo‐first‐order reaction rates of H2OOH+, H3NOH+, and protonated 4‐picoline‐N‐oxide towards isobutane and different halogenated alkanes CnH2n+1Cl (n=1–4), HCF3, CF4, and CF2Cl2 have been determined by means of Fourier transform ion cyclotron resonance meaurements. Reaction rates for H2OOH+ are generally fast (7.2×10−10–3.0×10−9 cm3 mol−1 s−1) and only in the cases HCF3 and CF4 no reactivity is observed. In contrast to this H3NOH+ only reacts with tC4H9Cl (kobs=9.2×10−10), while 4‐CH3‐C5H4N‐OH+ is completely unreactive. While H2OOH+ oxidizes alkanes by an initial hydride ion upon formation of a carbocation, it reacts with halogenated alkanes at the chlorine atom. Two mechanistic scenarios, namely oxidation at the halogen atom or proton transfer are found. Accurate proton affinities for HOOH, NH2OH, a series of alkanes CnH2n+2 (n=1–4), and halogenated alkanes CnH2n+1Cl (n=1–4), HCF3, CF4, and CF2Cl2, were calculated by using the G3 method and are in excellent agreement with experimental values, where available. The G3 enthalpies of reaction are also consistent with the observed products. The tendency for oxidation of alkanes by hydride ion is expressed in terms of G3 hydride affinities of the corresponding cationic products CnH2n+1+ (n=1–4) and CnH2nCl+ (n=1–4). The hypersurface for the reaction of H2OOH+ with CH3Cl and C2H5Cl was calculated at the B3 LYP, MP2, and G3m* level, underlining the three mechanistic scenarios in which the reaction is either induced by oxidation at the hydrogen or the halogen atom, or by proton transfer. Complexed OH+ ions, such as H2OOH+, H3NOH+ or iron porphyrinOH+ are the anticipated oxidants in many chemical reactions. Their reactivity alters tremendously with complexed ligand as was demonstrated for the reactions with halogenated alkanes in an FT‐ICR cell. The potential of H2OOH+ to oxidize halogenated alkanes (illustrated here) suggests that they may be of interest as an effective low‐cost detoxicant for problematic persistent halogenated hydrocarbons.